Pengaruh Media Big Book Modifikasi terhadap Kemampuan Membaca Anak: Studi pada Taman Kanak-Kanak Pertiwi 3 Siteba Padang - Nadya Meylisa Zahrah; Yulsyofriend (Lembaga Yasin AlSys, 2026)
The low reading ability of children at Pertiwi 3 Siteba Kindergarten, Padang, is indicated by difficulties in recognizing letter symbols, reading words accompanied by pictures, and arranging letters into words, as well as the limited variety of learning media used by teachers. This study aims to analyze the effect of using modified big book media on the reading ability of children aged 5–6 years at Pertiwi 3 Siteba Kindergarten, Padang. The study employed a quantitative approach with a quasi-experimental design. The study population comprised all children distributed across four classes, while the sample consisted of 20 children selected using purposive sampling and divided into an experimental group and a control group, with 10 children in each group. Data were collected through performance tests and observations using an instrument consisting of five items and were then analyzed using the Shapiro–Wilk normality test, homogeneity test, and independent-samples t-test with the assistance of SPSS 25 for Windows. The results showed that the mean score of the experimental group increased from 16.2 on the pretest to 18.2 on the posttest, whereas the mean score of the control group increased from 14.7 to 15.6. Hypothesis testing on the posttest yielded a two-tailed significance value of 0.020, which was lower than 0.05, indicating a significant difference between the experimental and control groups. Therefore, modified big book media had a significant effect on the reading ability of children aged 5–6 years. These findings provide practical implications for early childhood education teachers to use modified big book media as a more varied learning alternative for developing children’s ability to recognize letters, read words, and arrange letters into words.